PERANCANGAN MATERIAL CORAN BAJA LINK TRACK UNTUK BUCKET WHEEL EXCAVATOR BATUBARA - Beny Bandanadjaja; M. Achyarsyah (Badan Penelitian dan Pengembangan Daerah Provinsi Jawa Barat, 2015)
Link Track is a spare part of Bucket Wheel Excavator at Bukit Asam coal mine in West Sumatra. The spare partwas previously imported from Germany or India. The development of this product has been recomended by theuser of PT Bukit Asam Muara Enim to subtitize the imported product. On this research the material design ofLink Track has been obtained by Polman Bandung. The methods are included of material design and process,sampel cast, heat treatment, mechanical testing and metalography examination.the result shown that the bestcomposition of high tensile steel with alloying of Ni, Cr and Mo can reach high tensile strength which is properfor Link Track application. The heattreatment process which can obtain that result come from Normalizingprocess and followed by double reheating process of 650oC then second reheat on 650oC. The mechanicalproperties which is found is 683 Mpa, yield strength of 525 Mpa and elongation of 20 %.